The Population Dynamics of Belanger's Croaker (Johnius belangerii) at Barumun River, Panai Hilir District, Labuhanbatu Regency - Maryani, Sri; Machrizal, Rusdi (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2022)
This study aims to determine the population dynamics of J. belangerii fish in the waters of the Barumun River, Labuhanbatu Regency. Sampling was carried out for 3 months, starting in October – December 2021. The results showed the relationship between length and weight of J. belangerii fish was negative allometric with a b value of 0.713 (b<3). The population of J. belangerii was dominated by individual lengths between 14.5 - 38 cm with a body weight range of 30-80 grams. The length of the totic acid (L∞) is 41.55 cm with a growth coefficient (K) of 0.430 per year. Natural mortality (M) and fishing mortality (F) were 0.937 and 0.892 per year, respectively. The level of exploitation (E) obtained a value of 0.35 . The condition of the population of J. belangerii based on the value of (F),(N),(E) is not in a state of over-exploitation.ABSTRAK: Penelitian ini bertujuan untuk mengetahui dinamika populasi ikan J. belangerii yang ada di Perairan Sungai Barumun Kabupaten Labuhanbatu. Pengambilan sampel dilakukan selama 3 bulan, di mulai pada Oktober – Desember 2021. Hasil penelitian menunjukkan hubungan Panjang berat ikan J. belangerii adalah alometrik negatif dengan nilai b 0,713 (b<3). Populasi ikan J. belangerii didominasi ukuran panjang individu antara 14,5 - 38 cm dengan kisaran berat tubuh 30-80 gram. Panjang asim totik (L∞) adalah 41,55 cm dengan koefisien pertumbuhan (K) adalah 0,430 pertahun. Mortalitas alami (M) dan mortalitas penangkapan (F) masing-masing sebesar 0,937 dan 0,892 per tahun. Tingkat eksploitasi (E) diperoleh nilai 0,35 . Kondisi populasi J. belangerii berdasarkan nilai (F),(N),(E) tidak dalam keadaan over exploitasi.